Invasive Klebsiella pneumoniae Liver Abscess Syndrome Presenting with Septic Pulmonary Emboli, Hepatic Vein Thrombosis, Ascites and Endogenous Endophthalmitis: A Case Report - Venkatesan, Mugilan; Deb, Susmita (Indian Journal of Case Reports, 2026)
Invasive liver abscess syndrome (ILAS) caused by hypervirulent Klebsiella pneumoniae is characterized by a pyogenic liver abscess with hematogenous metastatic spread. Although commonly reported in East Asia, cases from India remain relatively uncommon. Diabetes mellitus is the most important predisposing factor. We report a case of a 44-year-old diabetic male who presented with community-acquired pneumonia complicated by ascites and septic shock. Persistent fever and worsening pulmonary infiltrates prompted further evaluation, which revealed a segment VI liver abscess, right hepatic vein thrombosis, and multiple septic pulmonary emboli. The patient also developed right-sided endogenous endophthalmitis due to metastatic spread. Blood and liver pus cultures grew Klebsiella pneumoniae. Ascitic fluid had high SAAG and high protein, secondary to hepatic vein thrombosis. Infective endocarditis and central nervous system involvement were excluded. The patient was managed with culture-directed meropenem therapy, pigtail drainage of the liver abscess, and intravitreal antibiotics, resulting in resolution of sepsis, although visual recovery remained limited. This case highlights that ILAS, which initially presented as community-acquired pneumonia, was subsequently identified as metastatic infection originating from a primary liver abscess. Invasive Klebsiella pneumoniae liver abscess is an emerging global threat that is being increasingly reported from India.